Reduced shoulder strength and change in range of motion are risk factors for shoulder injury in water polo players - Hams, A.; Evans, K.; Adams, R.; Waddington, G.; Witchalls, J. (Physical Therapy in Sport, 2019)
Pre-season TROM difference of =7.5° was a significant predictor for future episodes of shoulder injury. Shoulder IR strength PBW of =16.8% was a significant predictor for future episodes of shoulder injury. Shoulder ER strength PBW of =12.5% was a significant predictor for future episodes of shoulder injury.